The education role of hieroglyph in preserving cultural values of homeland in diaspora: a case study of the Chinese diaspora in Singapore - Kalashnyk, Lyubov (Professional Art Education, 2024)
Summary: This article explores the educational role of Chinese hieroglyphs in preserving cultural values of the homeland within the diaspora, focusing on the Chinese community in Singapore. The study examines how hieroglyphic writing serves as a cultural bridge, maintaining the identity and heritage of the Chinese diaspora while fostering a connection to their motherland. The aim of the research is to investigate how the use of hieroglyphs in everyday life contributes to cultural continuity among diaspora communities. Practical tasks include analysing the role of the Chinese in Singapore, exploring the role and balance between the Chinese characters and the official language in Singapore and find the ways it saves the Chinese culture and forms locality to Chinese state initiatives now. The research employs qualitative methods, including case studies and content analysis, to assess the effectiveness of hieroglyphs as cultural preservers. Results indicate that the use of hieroglyphs in community practices strengthens cultural retention and identity within the diaspora.
Keywords: PR China; Singapore; Chinese culture; Chinese character; hieroglyph; diaspora